Midwifery Care for Postpartum Mothers With Discomfort Suture Wound Pain In Maternity Hospital: Asuhan Kebidanan Pada Ibu Nifas Dengan Ketidaknyamanan Nyeri Luka Jahitan Di Rumah Sakit Bersalin - Azizah, Rizka Farikh; Djauharoh, Djauharoh; Azizah, Nurul (Indonesian Journal of Innovation Studies, 2020)
Postpartum is the period after delivery, the birth of the baby, the placenta and the complete membranes, which are needed to restore the reproductive organs and womb to their normal state before pregnancy, with a period of approximately 40-42 days or 6 months after delivery. During the puerperium, it is common to complain of pain at the stitches which can interfere with the comfort of the postpartum mother. This case study was conducted at RB & Clinic Afifa Prambon Sidoarjo which was conducted on January 5, 2020. This midwifery care was carried out by interviewing and obtaining data using the SOAP method. The results obtained from the care of physiological postpartum mothers were no complications and there was a gap between theory and practice.